2016
DOI: 10.1002/tox.22309
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in geometry, biomechanics, and mineral composition of juvenile rat femur induced by nonplanar PCB‐155 and/or planar PCB‐169

Abstract: Exposure to widespread lipophilic and bioaccumulative polychlorinated biphenyls (PCBs) induces diverse biochemical and toxicological responses in various organs, including the bone. The aim of this study was to evaluate the changes in growth rate, geometry, serum, and bone biochemical parameters and biomechanics of juvenile rat femur induced by lactational exposure to nonplanar PCB-155 and planar PCB-169 individually and in combination. Fifteen lactating Wistar rats were divided into four groups (PCB-169, PCB-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 63 publications
1
18
0
Order By: Relevance
“…Our preceding study on prepubertal rat offspring (PND 22) revealed inhibitory effects of dioxin-like PCB-169, but not nondioxin-like PCB-155, on femur growth and mineralization (Brankovič et al, 2017). However, we encountered problems when performing biomechanical measurements on the developing prepubertal bones, i.e., on PND 22, femurs were insufficiently mineralized to be precisely assessed in a three-6 point-bending test (Brankovič et al, 2017). This challenge was not the case in rats from PND 35 onwards (Finnilä et al, 2010;Indrekvam et al, 1991).…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…Our preceding study on prepubertal rat offspring (PND 22) revealed inhibitory effects of dioxin-like PCB-169, but not nondioxin-like PCB-155, on femur growth and mineralization (Brankovič et al, 2017). However, we encountered problems when performing biomechanical measurements on the developing prepubertal bones, i.e., on PND 22, femurs were insufficiently mineralized to be precisely assessed in a three-6 point-bending test (Brankovič et al, 2017). This challenge was not the case in rats from PND 35 onwards (Finnilä et al, 2010;Indrekvam et al, 1991).…”
Section: Introductionmentioning
confidence: 92%
“…A cerealbased fixed-formula maintenance diet for the rats (Altromin 1324, Lage, Germany) and water were administered ad libitum. After delivery, the mothers and their offspring were randomly divided into four groups and the PCB congener administration regimes with loading and maintenance doses were executed as previously described (Brankovič et al, 2017;Grošelj et al, 2014). This protocol was based on the TEF of PCB-169 (van den Berg et al, 2006) and the previously established excretion patterns of PCB-155 and PCB-169 in milk (Vrecl et al, 2005).…”
Section: Animals and Treatmentmentioning
confidence: 99%
See 3 more Smart Citations